2010
DOI: 10.1016/j.neuropsychologia.2010.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pure-tone pitch discrimination among persons with autism but not Asperger syndrome

Abstract: Persons with Autism spectrum disorders (ASD) display atypical perceptual processing in visual and auditory tasks. In vision, Bertone, Mottron, Jelenic, and Faubert (2005) found that enhanced and diminished visual processing is linked to the level of neural complexity required to process stimuli, as proposed in the neural complexity hypothesis. Based on these findings, Samson, Mottron, Jemel, Belin, and Ciocca (2006) proposed to extend the neural complexity hypothesis to the auditory modality. They hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
157
2
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(177 citation statements)
references
References 58 publications
14
157
2
4
Order By: Relevance
“…The majority of studies investigated more advanced pitch processing aspects like categorization, labelling, memory or disembedding, and they often used much more complex auditory stimuli or speech stimuli (e.g., Foxton et al 2003;Heaton 2003;Heaton et al 2005Heaton et al , 2008bJärvinen-Pasley and Heaton 2007;Järvinen-Pasley et al 2008a, b;Mottron et al 2000). Only three studies used a similar adaptive staircase procedure (as we did) to assess pure tone pitch processing (Bhatara et al 2013;Bonnel et al 2010;Jones et al 2009). The first psychoacoustic evidence for enhanced pitch discrimination of pure tones was provided by Bonnel et al (2003), who observed superior pitch discrimination in adolescents with autism and in adults meeting full criteria for autism but not in those with Asperger syndrome (Bonnel et al 2010).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The majority of studies investigated more advanced pitch processing aspects like categorization, labelling, memory or disembedding, and they often used much more complex auditory stimuli or speech stimuli (e.g., Foxton et al 2003;Heaton 2003;Heaton et al 2005Heaton et al , 2008bJärvinen-Pasley and Heaton 2007;Järvinen-Pasley et al 2008a, b;Mottron et al 2000). Only three studies used a similar adaptive staircase procedure (as we did) to assess pure tone pitch processing (Bhatara et al 2013;Bonnel et al 2010;Jones et al 2009). The first psychoacoustic evidence for enhanced pitch discrimination of pure tones was provided by Bonnel et al (2003), who observed superior pitch discrimination in adolescents with autism and in adults meeting full criteria for autism but not in those with Asperger syndrome (Bonnel et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Only three studies used a similar adaptive staircase procedure (as we did) to assess pure tone pitch processing (Bhatara et al 2013;Bonnel et al 2010;Jones et al 2009). The first psychoacoustic evidence for enhanced pitch discrimination of pure tones was provided by Bonnel et al (2003), who observed superior pitch discrimination in adolescents with autism and in adults meeting full criteria for autism but not in those with Asperger syndrome (Bonnel et al 2010). Partial support for this finding was provided by Jones et al (2009), who found no differences in frequency discrimination at the group level, but who identified a subgroup of adolescents with ASD and delayed language onset who showed exceptional frequency categorization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for enhanced frequency discrimination ability of isolated pure tone stimuli has been found in children with ASD (Bonnel et al, 2003;Heaton, et al, 2008;O'Riordan and Passetti, 2006) and in adults with autism (although not in adults with Asperger's syndrome) in combined four-interval with two-forced choice (2IFC) frequency discrimination tasks (Bonnel et al, 2010). Furthermore, a similar pattern of ability has been observed also at neural levels in electrophysiological studies investigating neural response to changes of frequency in individuals with ASD, at the pre-attentive level (Ferri et al, 2003;Gomot et al, 2011;Gomot, Giard, Adrien, Barthelemy, and Bruneau, 2002;Kujala et al, 2010;Lepistö et al, 2008;.…”
mentioning
confidence: 99%